(untitled) (American Journal of Islam and Society, 1989)
The International Seminar on Islamic Economics and the Economy of Indian Muslims was held July 21-24, 1989 in the Convention Center of Hamdard University, New Delhi, India, under the auspices of the Institute of Objective Studies (IOS). The Seminar was the first of its kind in India. There were 10 sessions, with over 60 participants, on various aspects of Islamic Economics as well as on the economy of Indian Muslims. In addition there were inaugural and plenary sessions, and a public lecture. All the sessions were well-attended. Conference delegates and participants came from all over India, as well as Egypt and the U.S. A number of scholars from other countries could not attend the Conference because of the denial of visa for attending the Conference by the Indian Embassies in their respective countries. The Conference convened on Friday, July 21, 1989 at 1190 A.M. with the inaugural session chaired by Dr. S. Z. Qasim, Vice-Chancellor of Jamia Millia Islamia, New Delhi. After the welcome speech by Mr. A. R. Agwan, Director of the IOS, Dr. Manzoor Alam, Chairman of the IOS, introduced the 10s and its activities. The inaugural address was delivered by Dr. A. R. Kidwai, Chancellor, Aligarh Muslim University (AMU). Following that, the keynote address was given by Dr. F. R. Faridi of AMU, who was also the convenor of this seminar. Among the foreign delegates were Dr. Shawki Ismail Shehata of Faisal Islamic Bank of Egypt, Prof. Syed Iqbal Mahdi (who is the Secretary of the AMSS Economics Discipline Group),and Dr. A. Q. J. Shaikh from the U.S.A., and Dr. M. Ayub Munir from Pakistan. The Conference organizers had carefully selected the topics which were timely and relevant both in terms of Islamic economics and the economy of Indian Muslims. Each session had 4 to 5 papers. The following were some of the topics: 1. Employment Situation of Indian Muslims: An Appraisal of its Nature and Magnitude 2. Islamic Banking: Theory and Practice 3. An Islamic Approach to Economic Development ...